Clinical and parental age characteristics of rare copy number variant burden in patients with schizophrenia. Issue 5 (5th May 2015) - Martin, Andrew K.; Robinson, Gail; Reutens, David; Mowry, Bryan
Abstract : Copy number variant (CNV) burden, especially for rare deletions, has been associated with risk for schizophrenia as well as phenotypic differences within cognitive and neuroimaging domains. The current study investigated clinical and parental age characteristics of rare CNV burden in patients with schizophrenia. Clinical data was collected for 629 patients with schizophrenia who formed part of a genomewide association study, which included CNV data. Parental age was available for 368 patients. Correlations were calculated between burden scores and positive, negative, and mood symptoms from the Lifetime Diagnostic Psychosis Scale as well as age at onset. Patients were grouped according to number of rare deletions, duplications, or total CNVs and MANOVAs used to investigate differences in clinical and parental age characteristics. Patients with the least number of CNVs had older fathers and larger parental age difference. Patients with no deletions had older mothers and those with five or more deletions had younger mothers. Total deletion, duplication, and CNV burden, as measured by number of base pairs, were not associated with clinical or parental age differences although total rare duplication burden had a negative correlation with positive symptoms that did not survive correction for multiple testing. Likewise, a positive correlation between age at onset and total CNV burden did not survive correction. Rare CNVs are associated with differences in parental age in patients with schizophrenia. No robust clinical differences were identified. However, duplication burden may have a small protective effect against positive symptoms and age at onset may be influenced by total CNV burden. No clinical differences were associated with deletion burden measures. © 2015 Wiley Periodicals, Inc.